Flowering induction of Aster ericoides (L.) using gibberellic acid - Naranja, Leonido R.; Balladares, Maria Charito E. (2008)
The effect of gibberellic acid on bolting and flower characteristics of Baby Aster [Aster ericoides (L.)] was investigated. Five concentrations (0,10, 30, 50 and 100 ppm) of GA3 (Berelex®, 10 % GA3) were used. The diluted chemical was sprayed to the leaves of the sucker divisions 30 d after planting and repeated 1 wk later. Bolting was observed in plants sprayed with 100 ppm GA310.7 d from spraying. The plants that received 50, 30 and 10 ppm GA3 bolted 11.8, 16.5 and 25.8 d from spraying, respectively. The control bolted 53.5 d after spraying although some plants in this group remained vegetative until the end of the experimental period. One hundred percent flowering was observed in plants sprayed with GA3 and only 55.7% flowering in the control plants. Harvesting was 48 d from bolting for the treated plants compared with 58 d for the control plants. All treated plants were much taller than the control plants (69.8 cm). The 30 ppm-treated plants were tallest at 80.6 cm while the 10, 50 and 100 ppm- sprayed plants at 75.4, 76.6, 77.5 cm, respectively, were shorter and not significantly different from one another. Flower stalk weight was not affected by the treatments. Simple cost and benefit analysis showed that the highest net income of PhP 58,260 per cropping season was obtained from 50 ppm GA3 spraying of aster planted in a 600-m2 field. This income is 50% more than that from the untreated or light-supplemented plants. Since the 50 ppm GA3-sprayed plants bolted early, gave the highest net profit and were heaviest although not significantly different from the other treatments, this dose is recommended for the commercial growing of aster. Aster is sold in the market by the weight of the inflorescence.
Keywords: Flowers -- Varieties